The reception of Aristotle’s theory of chance in Alexander of Aphrodisias’ De Fato - Ross Hernández, Alberto (Estudios de Filosofía, 2009)
this paper deals with the reception and transformation of Aristotle’s theory of chance and causality in one of the fundamental works of ancient aristotelism: Alexander of Aphrodisias’ De Fato. Ross suggests a continuity between Aristotle and Alexander in some of the most important tenets of Alexander’s proposal. Ross points out some of the most significant differences between the two philosophers in the context of a more general discussion on the relation between the physical world and the metaphysical entities. According to Ross, Alexander introduced some notions into the Aristotelian philosophy, such as “fate” and “providence”, which are entirely alien to Aristotle’s original theses and diverge from the words of the Master in more than one occasion, even though he attributes to him his own doctrine. Finally, Ross attempts to show that there is a tension between the traditional reading of Metaphysics XII –inspired in Alexander– and some theses of Alexander’s De Fato. The view that the First Mover presents itself as something desirable and understandable to the first heaven, which moves in a circle to imitate the actuality of that which is presented as desireable and whose only activity is thinking of itself, is inspired, according to Ross, precisely Alexander.